2014
DOI: 10.1371/journal.pone.0104441
|View full text |Cite
|
Sign up to set email alerts
|

The Octopamine Receptor Octβ2R Regulates Ovulation in Drosophila melanogaster

Abstract: Oviposition is induced upon mating in most insects. Ovulation is a primary step in oviposition, representing an important target to control insect pests and vectors, but limited information is available on the underlying mechanism. Here we report that the beta adrenergic-like octopamine receptor Octβ2R serves as a key signaling molecule for ovulation and recruits protein kinase A and Ca2+/calmodulin-sensitive kinase II as downstream effectors for this activity. We found that the octβ2r homozygous mutant female… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
103
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(114 citation statements)
references
References 51 publications
9
103
2
Order By: Relevance
“…In D. melanogaster, octopamine was found to increase the contractions of the peritoneal sheath, a contractile meshwork that surrounds the ovary, and to relax the oviducts, thereby enabling the release of eggs into the oviducts (Middleton et al, 2006). Moreover, Octβ2R and OAMB have been found to be the receptors associated with the process of ovulation and fertilization in Drosophila (Lee et al, 2003;Li et al, 2015;Lim et al, 2014). Deletions in the oamb locus and mutant constructs of Octβ2R resulted in accumulation of eggs in the ovary and a significant decrease in the number of eggs laid (Lee et al, 2003;Li et al, 2015;Lim et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In D. melanogaster, octopamine was found to increase the contractions of the peritoneal sheath, a contractile meshwork that surrounds the ovary, and to relax the oviducts, thereby enabling the release of eggs into the oviducts (Middleton et al, 2006). Moreover, Octβ2R and OAMB have been found to be the receptors associated with the process of ovulation and fertilization in Drosophila (Lee et al, 2003;Li et al, 2015;Lim et al, 2014). Deletions in the oamb locus and mutant constructs of Octβ2R resulted in accumulation of eggs in the ovary and a significant decrease in the number of eggs laid (Lee et al, 2003;Li et al, 2015;Lim et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Octβ2R and OAMB have been found to be the receptors associated with the process of ovulation and fertilization in Drosophila (Lee et al, 2003;Li et al, 2015;Lim et al, 2014). Deletions in the oamb locus and mutant constructs of Octβ2R resulted in accumulation of eggs in the ovary and a significant decrease in the number of eggs laid (Lee et al, 2003;Li et al, 2015;Lim et al, 2014). Similarly, in R. prolixus, octopamine reduced the amplitude of oviduct contractions, probably by binding to OctβR, leading to an elevation in cAMP levels and muscle relaxation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these effects are enhanced locomotion and flight muscle performance (Pribbenow and Erber, 1996;Saraswati et al, 2004;Fussnecker et al, 2006;Bloch and Meshi, 2007;Vierk et al, 2009), both direct and indirect mobilization of fat stores (Roeder, 2005), as well as increases in cardiac and respiratory rates (Zornik et al, 572 Gainetdinov et al 1999). OCT-mediated regulation of immune responses (Huang et al, 2012) and a role in reproductive behavior have also been reported (Lee et al, 2003;Lim et al, 2014). In the firefly, OCT is well established to underlie the neural basis of light emission (Copeland and Robertson, 1982;Christensen et al, 1983;Hashemzadeh et al, 1985) and also regulates bioluminescent emissions in glow worms (Rigby and Merritt, 2011).…”
Section: E Physiologic Responsesmentioning
confidence: 95%